Designing a Website-Based Technology Winnicode News Portal Application with Prototyping Method to Enhance User Engagement for Technology News Reader - Sekar Wangi, Sari Asih; Winarsih, Nurul Anisa Sri (Universitas Medan Area, 2025)
A news portal is a platform that usually takes the form of a website that presents various kinds of news according to its type. With the development of technology and the emergence of social media, the audience of these news portal websites has decreased. People prefer to read news through social media pages because they are easier to access. Based on this, it is necessary to develop an efficient and eye-friendly news portal website to attract people to read news through the website. By using the prototype method, the website is designed based on a pre-made design. So that the developers have a benchmark in developing the website to be built. After that, an evaluation is needed from user reviews and testing is carried out gradually to improve the website to make it more efficient and appropriate. Of the 10 test points that have been carried out in the study, a 100 percent success rate has been achieved from the test. This shows that the performance of the website that has been built can meet the criteria to be published and can be used by the wider community. From the development of this application, people can read with the theme of technology that is more comfortable, easily accessible and can send criticism to the publisher if there is a mismatch of news, have additional information about the latest news, or suggestions for the website so that it can be developed